Economic analysis of two-stage septic revision after total hip arthroplasty: What are the relevant costs for the hospital's orthopedic department?. Issue 1 (December 2016) - Kasch, R.; Assmann, G.; Merk, S.; Barz, T.; Melloh, M.; Hofer, A.; Merk, H.; Flessa, S.
Abstract Background The number of septic total hip arthroplasty (THA) revisions is increasing continuously, placing a growing financial burden on hospitals. Orthopedic departments performing septic THA revisions have no basis for decision making regarding resource allocation as the costs of this procedure for the departments are unknown. It is widely assumed that septic THA procedures can only be performed at a loss for the department. Therefore, the purpose of this study was to investigate whether this assumption is true by performing a detailed analysis of the costs and revenues for two-stage septic THA revision. Methods Patients who underwent revision THA for septic loosening in two sessions from January 2009 through March 2012 were included in this retrospective, consecutive cost study from the orthopedic department's point of view. We analyzed variable and case-fixed costs for septic revision THA with special regard to implantation and explantation stay. By using marginal costing approach we neglected hospital-fixed costs. Outcome measures include reimbursement and daily contribution margins. Results The average direct costs (reimbursement) incurred for septic two-stage revision THA was €10, 828 (€24, 201). The difference in cost and contribution margins per day was significant (p  < .001 andp  = 0.019) for ex- and implantation (€4147 vs. €6680 and €429 vs. €306) while length of stay and reimbursement were comparable. Conclusions This is the first detailed analysis of the hospital department's cost for septic revision THA performed in two sessions. Disregarding hospital-fixed costs the included variable and case fixed-costs were covered by revenues. This study provides cost data, which will be guidance for health care decision makers.